Investigation of the cytoplasmic pool of centriolar and centrosomal proteins - Steinacker, TL (2021)
How cells control the size and number of their organelles is largely unclear. In the Raff laboratory, we study centriole and centrosome biogenesis to investigate how their assembly is dynamically regulated. Centrioles are barrel-shaped cell organelles that, in preparation for mitosis, can give rise to the centrosome, an amorphous, protein-dense structure. In Drosophila, only a small number of proteins are essential for the formation of both organelles: centrioles require the five core duplication proteins Asl, Plk4, Ana2, Sas-6 and Sas-4, and the underlying centrosomal scaffold is formed by an interplay of Polo, Spd-2, and Cnn. By using the early Drosophila embryo as a model system, we can simultaneously observe the incorporation dynamics of fluorescently tagged proteins of interest at a large number of centrioles and centrosomes. Ultimately, we would like to mathematically model both assembly processes, but we lack information regarding how the cytoplasmic pool of their individual building blocks behaves during organelle formation. I therefore optimised and developed novel spectroscopy techniques for the early Drosophila embryo, including Fluorescence correlation spectroscopy, Fluorescence cross-correlation spectroscopy, and Peak counting spectroscopy. I then used these techniques to assess the biophysical properties of the embryo’s syncytial cytoplasm and conducted a systematic characterisation of the core proteins’ cytoplasmic concentration, diffusion dynamic, and average cytoplasmic stoichiometry.